Psychiatric Care Policy in Greece in the First Half of the 20th Century - Douki, Stamatina; Tzagkarakis, Stylianos Ioannis; Karakatsani, Despoina (HAPSc Policy Briefs Series, 2021)
Psychiatric care in Greece followed a similar course to the rest of Europe with a significant difference, the delay in the creation of asylum. The present study aims to investigate a) the development of psychiatric hospitals in the Greek state as well as the historical and social context from the beginning to the middle of the 20th century and b) the formulation of the Psychiatric Reform (PR) program. The methodology followed included literature and research data review, which were collected through online databases, publications, articles, journals, and dissertations. A crucial outcome of the study is that the obvious gaps and the very serious shortages of psychiatric care in Greece, during the previous decades, were not enough to point out the necessity of a Psychiatric Reform (PR), but were only perceived as another imposed obligation towards europeanization.